Problem budżetowania kosztów uczelni państwowej w warunkach nowej ustawy Prawo o szkolnictwie wyższym - zarys problemu - Ćwiąkała-Małys, Anna (The Problem of Cost Budgeting in a Public College under a New Act on Higher Education, 2006)
The article shows the problems of budgeting in a public college under conditions of a new Polish law: Act on Higher Education. The necessity of changing the way of cost calculation in the process of teaching is indicated. The paper presents the model of more effective (rational) system of calculation of teaching costs. This model shows how to use endowments received by colleges in a better way.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 48-55